Trade practices are main factors involved in the transmission of viral haemorrhagic septicaemia. Issue 2 (30th September 2012) - Reichert, M; Matras, M; Skall, H F; Olesen, N J; Kahns, S
Abstract: Viral haemorrhagic septicaemia (VHS), caused by the novirhabdovirus viral haemorrhagic septicaemia virus (VHSV), causes significant economic problems to European rainbow trout, Oncorhynchus mykiss (Walbaum), production. The virus isolates can be divided into four distinct genotypes with additional subgroups. The main source of outbreaks in European rainbow trout farming is sublineage Ia isolates. Recently, this group of isolates has been further subdivided in to two subclades of which the Ia‐2 consists of isolates occurring mainly in Continental Europe outside of Denmark. In this study, we sequenced the full‐length G‐gene sequences of 24 VHSV isolates that caused VHS outbreaks in Polish trout farms between 2005 and 2009. All these isolates were identified as genotype Ia‐2; they divided however into two genetically distinct subgroups, that we name Pol I and Pol II. The Pol I isolates mainly caused outbreaks in the southern part of Poland, while Pol II isolates predominantly were sampled in the north of Poland, although it seems that they have been transmitted to other parts of the country. Molecular epidemiology was used for characterization of transmission pathways. This study shows that a main cause of virus transmission appears to be movement of fish. At least in Polish circumstances trading practices appear to have significant impact on spreading of VHSV infection.